2017
DOI: 10.1186/s12886-017-0420-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of intravitreal ranibizumab therapy on diabetic macular edema

Abstract: BackgroundThe short-term effects of intravitreal ranibizumab (IVR) on diabetic macular edema (DME) remains unclear. We assessed the short-term effects of IVR on DME.MethodsEighteen eyes of 14 patients with DME were enrolled in this prospective interventional case series. After intravitreal ranibizumab was injected into treatment-naïve eyes with DME, we measured the foveal thickness (FT) before and 2 h, 1 day, 1 week, and 1 month later and the best-corrected visual acuity (BCVA) at all times except 2 h and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Similarly, Gonzalez reported that the BCVA at 12 weeks after a ranibizumab injection for DME was significantly associated with the outcome at 3 years [ 9 ]. In addition, two other studies have reported that the short-term effects (1 day to 3 months) can predict the therapeutic outcome of the anti-VEGF treatment for DME [ 10 , 11 ]. Thus, the earlier prediction is desirable from a patient’s burden, and it would be ideal if the therapeutic effects could be predicted only by the response to the first injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Gonzalez reported that the BCVA at 12 weeks after a ranibizumab injection for DME was significantly associated with the outcome at 3 years [ 9 ]. In addition, two other studies have reported that the short-term effects (1 day to 3 months) can predict the therapeutic outcome of the anti-VEGF treatment for DME [ 10 , 11 ]. Thus, the earlier prediction is desirable from a patient’s burden, and it would be ideal if the therapeutic effects could be predicted only by the response to the first injection.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the sample size needed for power with an effect size of 0.3, α-error of 0.05, and power of 0.95, and found that the total sample size was estimated to be 34 for each group. Although there is a possibility of a small sample size for our study, previous similar studies also reported that short-term effects can predict the therapeutic outcome of the anti-VEGF treatment of DME with a small number of fewer than 20 eyes [ 10 , 11 ]. Therefore, we believe that our results are reliable for determining short-term effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although antivascular endothelial growth factor (VEGF) treatment remains the first-line treatment for DME, the use of adjunct laser treatment has been shown to reduce the number of injections necessary for patient management [ 29 43 ]. The results of future clinical studies are needed to corroborate our present findings and validate the utility of subthreshold photocoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) who demonstrated that there was a significant (p < 0.05) correlation between the Δ CMT-1w and ΔVA-1w in the present study. Further researches with a large sample size are required to verify the association between the improvements in BCVA and improvements in CMT 35 .…”
Section: In the Same Line Comparable Duration Was Recorded Bymentioning
confidence: 99%